An overview of biodegradable nanomaterials and applications in vaccines. Issue 5 (29th January 2020) - Yan, Xingye; Zhou, Mo; Yu, Shuang; Jin, Zheng; Zhao, Kai
Abstract: Vaccination is the most cost-effective and sustainable way to prevent and eliminate infectious diseases. Compared with traditional vaccines, novel vaccines have better stability, longer duration and require less antigen usage. In addition, novel vaccines have better immune effects and significantly less toxic side effects. However, both novel vaccines and traditional vaccines require carrier molecules or adjuvants to produce an optimal immune response. There is an increasing demand for vaccine adjuvants and delivery systems that can induce stronger immune response whilst reducing production cost and the dose of vaccine. In recent years, nanotechnology has played an important role in the development of novel vaccine adjuvants and nano-delivery systems. Biodegradable materials have also received a lot of attention in medical science because they have excellent biocompatibility, biodegradability and low toxicity, which can protect antigens from degradation, increase antigen stability and provide slow release; resulting in enhanced immunogenicity. Therefore, biodegradable nanoparticles have attracted much attention in the formulation of vaccines. In this review, we outline some key features of biodegradable nanomaterials in the developing safer and more effective vaccines. The properties, structural characteristics, advantages and disadvantage of the biodegradable nanomaterials will be systematically reviewed. Additionally, applications, research progress and future prospects of biodegradable nanomaterials are discussed. This review will be help in future research work directed at developing biodegradable vaccine adjuvants or delivery carriers.